2020
DOI: 10.3847/1538-4357/ab9809
|View full text |Cite
|
Sign up to set email alerts
|

Polluting the Pair-instability Mass Gap for Binary Black Holes through Super-Eddington Accretion in Isolated Binaries

Abstract: The theory for single stellar evolution predicts a gap in the mass distribution of black holes (BHs) between approximately 45 and 130  M , the so-called "pair-instability mass gap." We examine whether BHs can pollute the gap after accreting from a stellar companion. To this end, we simulate the evolution of isolated binaries using a population synthesis code, where we allow for super-Eddington accretion. Under our most extreme assumptions, we find that at most about 2% of all merging binary BH systems contain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 147 publications
1
58
0
Order By: Relevance
“…An important future step will be to incorporate the stellar physics embedded in our prescription (Equation ( 5)) into the description of the pollutant population. In addition to second-generation black holes, this population will contain objects with significant postcollapse accretion (van Son et al 2020;Belczynski 2020) and also black holes formed after non-isolated, pre-collapse stellar mergers (Di Carlo et al 2020;Kremer et al 2020;Renzo et al 2020), all of whose mass functions and contributions to the merger rate should eventually be modeled appropriately and independently. Likewise, including primordial black holes (PBHs) will require a different population model (Hütsi et al 2021;De Luca et al 2021).…”
Section: Bhmentioning
confidence: 99%
“…An important future step will be to incorporate the stellar physics embedded in our prescription (Equation ( 5)) into the description of the pollutant population. In addition to second-generation black holes, this population will contain objects with significant postcollapse accretion (van Son et al 2020;Belczynski 2020) and also black holes formed after non-isolated, pre-collapse stellar mergers (Di Carlo et al 2020;Kremer et al 2020;Renzo et al 2020), all of whose mass functions and contributions to the merger rate should eventually be modeled appropriately and independently. Likewise, including primordial black holes (PBHs) will require a different population model (Hütsi et al 2021;De Luca et al 2021).…”
Section: Bhmentioning
confidence: 99%
“…As discussed in detail in [2], the likelihood of hierarchical mergers depends strongly on the natal environment and the details of the initial black hole formation, but a larger number of high-precision events will enable statistical analysis of these effects. Alternatively, super-Eddington accretion (from common-envelope evolution or stable mass transfer) may "pollute" the mass gap [18,19], but a recent study in the context of a population synthesis model found no pairs with combined mass in excess of 100M [20]. These mechanisms for mass increase after black hole birth, though beset by uncertainties, will be better understood with dedicated modeling and additional observational constraints from future LIGO/Virgo runs.…”
Section: Gw190521mentioning
confidence: 99%
“…Measuring the bounds of the PISN mass gap will provide insights into stellar evolution and fundamental physics (Talbot & Thrane 2018;Farr et al 2019;Farmer et al 2019;van Son et al 2020). However, one needs to account for the dynamical processes that can lead to black holes in this mass range.…”
Section: Introductionmentioning
confidence: 99%